1997
DOI: 10.1046/j.1464-410x.1997.02849.x
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional interferon in the treatment of Peyronie's disease: a pilot study

Abstract: Objective  To investigate the effect of intralesional interferon on patients with severe Peyronie's disease. Patients and methods  Thirteen patients with Peyronie's disease and associated penile deformity of greater than 12 months' duration were selected. Characteristics of the plaque and the degree of deformity were measured objectively. Ten patients received 1.5 MU of α2B‐interferon intralesionally three times a week for 3 weeks. Three patients received similar volumes of intralesional saline. Results  Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 0 publications
1
36
2
6
Order By: Relevance
“…45,46 Furthermore, interferon alpha 2b is recognized to effectively decrease keloid scars and scleroderma. 47 Based on the success of intralesional collagenase and verapamil and the recognized in vitro effects of interferon alpha, the first report with intralesional interferon alpha 2b demonstrated decreased penile pain, penile curvature, and plaque size. 43,47,48 In summary, the antioxidants are both natural and synthetic compounds (Table 1), and have recently gained considerable attention by the nutritional, cosmetic, and pharmaceutical industries.…”
Section: Role Of Antioxidants In Peyronie's Diseasementioning
confidence: 99%
“…45,46 Furthermore, interferon alpha 2b is recognized to effectively decrease keloid scars and scleroderma. 47 Based on the success of intralesional collagenase and verapamil and the recognized in vitro effects of interferon alpha, the first report with intralesional interferon alpha 2b demonstrated decreased penile pain, penile curvature, and plaque size. 43,47,48 In summary, the antioxidants are both natural and synthetic compounds (Table 1), and have recently gained considerable attention by the nutritional, cosmetic, and pharmaceutical industries.…”
Section: Role Of Antioxidants In Peyronie's Diseasementioning
confidence: 99%
“…47 Intralesional injection of either alpha 2A or alpha 2B interferon have also been reported with mixed results. 48,49 Oral tamoxifen has been tested as a therapeutic agent to treat Peyronie's disease. 50 Tamoxifen, an anti-estrogen, is thought to work by inducing TGF-b 1 expression.…”
Section: Molecular Mechanisms: Oxidative Damage and The Role Of Free mentioning
confidence: 99%
“…34,35 Judge et al, found a minimal positive objective effect on patients with smaller plaques, while Lue argued against the effectiveness of local interferon in 1998. 36,37 Ahuja et al, reported a signi®cant improvement in pain and curvature in their 1999 article. 38 Our ®ndings suggest that alpha-interferon has a signi®cant inhibitory effect on the proliferation of ®broblasts in vitro.…”
Section: Discussionmentioning
confidence: 98%